(untitled) (The Agriculturists, 2012)
The present study attempted to determine the economic returns of alternative farming system of integrated farming aiming to address the livelihood security of small farm households. One hundred and sixty small and medium farmers practicing in four different FS such as Crop-Poultry (C-P), Crop-Poultry-Pond fisheries (C-P-F), Crop-Livestock-Poultry (C-L-P) and Crop-Livestock-Poultry-Pond fisheries (C-L-P-F) were selected from Mymensingh, Jamalpur and Sherpur district. The main information collected were socio-demographic characteristics of farm households, household income from farm and non-farm sources, size of land holding and farming system followed, livestock and poultry rearing and pond fish culture, and effect of integrated farming on household income and livelihood security of small farm households. Data were collected covering one production period during 2009-2010. For estimating farm income of small farm household, whole farm approach was considered. Increased number of farm enterprises caused higher farm income. However, considering the small farm practices and whole farm approach, the farm income as well as net return was higher for C-L-P-F farmers (Tk. 57002), followed by C-L-P (Tk. 52978), C-P-F (Tk. 20447) and C-P (Tk. 13734) farmers. Some of the most commonly used factors in the assessment of livelihood security included those related to household income and expenditure, expenditure spent on food, adequacy of food taken, household structure and facilities, owning household assets, and access to drinking water and sanitation, and other basic needs of farm household. All these socioeconomic factors were found to be related livelihood security of small farmers in Bangladesh. Women were more involved in income earning activities and household decision making with the introduction of integrated farming in small farm condition. DOI: http://dx.doi.org/10.3329/agric.v10i1.11065 The Agriculturists 2012; 10(1): 51-63